Video Intervention In Health Education Use Case Study To Improve Understanding Of Tuberculosis - Mustopa, Raden; Damris, Damris; Syamsurizal , Syamsurizal; Guspianto, Guspianto (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Tuberculosis is a deadly infectious disease in the world. Five countries account for 56% of the world total: India (26%), Indonesia (10%), China (6.8%), the Philippines (6.8%) and Pakistan (6.3%). One of the biggest challenges in controlling TB is the lack of public knowledge about how it is transmitted, early symptoms, and the importance of undergoing complete treatment. The shift from traditional health promotion methods to digital media, especially video, offers a more engaging and effective way of conveying health information. This research uses a quantitative approach with a pre-test and post-test design without a control. This study involved 175 respondents who lived around TB patients, selected purposively on 5–30 June 2024 in the Pakuanbaru Health Center and Putriayu Health Center areas, Jambi City. Data analysis was carried out using the T-Test to measure changes in knowledge before and after the educational intervention. The results showed that the average pre-test score was 66 with a minimum score of 27 and a maximum of 93. After the intervention, the average post-test score increased significantly to 85, with a minimum score of 60 and a maximum of 100. Statistical analysis showed a significant increase in participant knowledge, with an average difference in scores between the pre-test (mean = 9.97; SD = 2.010) and post-test (mean = 12.79; SD = 2.186). The t-test produced a significance value (p <0.01), indicating that the video intervention had a positive impact on increasing participants' understanding of the educational material presented.